UZBEK LITERATURE FOR PRIMARY SCHOOL CHILDREN - Khikmatullayeva Durdona; Yusupov Asror Raimqul ugli (TADQIQOTLAR.UZ, 2023)
Abstract: Indeed, in carrying out this serious task, more precisely, in raising the generation of an independent country mature in all aspects, the incomparable Uzbek children's literature, which has become a reality on the basis of centuries-old folk traditions, national values, folklore examples, traditions of our national literature and the literature of the world nations. there is a place. For more than half a century, pedagogical universities and colleges students of primary education, preschool education are studying this subject in depth. There is no doubt that the textbooks and manuals published in the field of children's literature during this period have been a spiritual and spiritual force in educating the young generation.